2016
DOI: 10.1371/journal.pone.0166979
|View full text |Cite
|
Sign up to set email alerts
|

Natural Schistosoma mansoni Infection in the Wild Reservoir Nectomys squamipes Leads to Excessive Lipid Droplet Accumulation in Hepatocytes in the Absence of Liver Functional Impairment

Abstract: Schistosomiasis is a neglected tropical disease of a significant public health impact. The water rat Nectomys squamipes is one of the most important non-human hosts in the schistosomiasis mansoni transmission in Brazil, being considered a wild reservoir. Cellular mechanisms that contribute to the physiological adaptation of this rodent to the Schistosoma mansoni parasite are poorly understood. Here we identified, for the first time, that a hepatic steatosis, a condition characterized by excessive lipid accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 56 publications
(71 reference statements)
5
33
0
Order By: Relevance
“…Both naturally and experimentally infected animals and their respective uninfected controls were anesthetized and euthanized as before [ 19 ], and organ fragments were collected and processed for histopathological studies as below. Animals were euthanized by exsanguination (full bleed) under deep anesthesia by cardiac puncture.…”
Section: Methodsmentioning
confidence: 99%
“…Both naturally and experimentally infected animals and their respective uninfected controls were anesthetized and euthanized as before [ 19 ], and organ fragments were collected and processed for histopathological studies as below. Animals were euthanized by exsanguination (full bleed) under deep anesthesia by cardiac puncture.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, a wide range of liver damage has been described in both human and animal infections. These include impaired protein synthesis 4 , reduced lipoprotein concentrations [5][6][7][8] , decreased erythrocyte counts and blood indexes, neutropenia, lymphopenia and eosinophilia 9 , increased circulating liver enzymes levels 10,11 , and hemostatic abnormalities 12,13 . Despite the variability in clinical signs, it remains unclear whether infected individuals without clinical complaints or symptoms present a detectable degree of liver dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Raman imaging could locate and quantify the proportion of LDs in HuH7 cells under different feed conditions; such a quantification has relevance in the disease conditions. 41,42 Previous Raman imaging studies have also shown the capability of the technique to detect LDs in cells by mapping lipids. 43-47 However, molecular mapping of many different constituents of LD has never been demonstrated.…”
Section: Discussionmentioning
confidence: 99%